Differential impact of non-pharmaceutical public health interventions on COVID-19 epidemics in the United States - Xiaoshuang Liu; Xiao Xu; Guanqiao Li; Xian Xu; Yuyao Sun; Fei Wang; Xuanling Shi; Xiang Li; Guotong Xie; Linqi Zhang (BMC, 2021)
Abstract Background The widespread pandemic of novel coronavirus disease 2019 (COVID-19) poses an unprecedented global health crisis. In the United States (US), different state governments have adopted various combinations of non-pharmaceutical public health interventions (NPIs), such as non-essential business closures and gathering bans, to mitigate the epidemic from February to April, 2020. Quantitative assessment on the effectiveness of NPIs is greatly needed to assist in guiding individualized decision making for adjustment of interventions in the US and around the world. However, the impacts of these approaches remain uncertain. Methods Based on the reported cases, the effective reproduction number (R t ) of COVID-19 epidemic for 50 states in the US was estimated. Measurements on the effectiveness of nine different NPIs were conducted by assessing risk ratios (RRs) between R t and NPIs through a generalized linear model (GLM). Results Different NPIs were found to have led to different levels of reduction in R t . Stay-at-home contributed approximately 51% (95% CI 46-57%), wearing (face) masks 29% (15-42%), gathering ban (more than 10 people) 19% (14-24%), non-essential business closure 16% (10-21%), declaration of emergency 13% (8-17%), interstate travel restriction 11% (5-16%), school closure 10% (7-14%), initial business closure 10% (6-14%), and gathering ban (more than 50 people) 7% (2-11%). Conclusions This retrospective assessment of NPIs on R t has shown that NPIs played critical roles on epidemic control in the US in the past several months. The quantitative results could guide individualized decision making for future adjustment of NPIs in the US and other countries for COVID-19 and other similar infectious diseases.